Latvijas Republikas un Krievijas Federācijas valdību attiecības Latvijas neatkarības atjaunošanas periodā (1990. gada 4. maijs – 1991. gada 21. augusts) - Ļebedeva, Maija (Latvijas Universitāte, 2006)
Darbs “Latvijas Republikas un Krievijas Federācijas valdību attiecības Latvijas neatkarības atgūšanas periodā” ir par Latvijas un Krievijas valdību attiecībām Latvijas divvaldības periodā no 1990.gada 4.maija, kad tika deklarēta Latvijas neatkarība līdz 1991.gada 21.augustam, kad Latvijas Augstākā Padome pieņēma Konstitucionālo likumu par valstisko statusu un tādējādi atjaunoja Latvijas neatkarību pilnībā. Darbā pamatā atainota Latvijas un Krievijas valdību sadarbība attiecībā pret PSRS centru, savu izvirzīto mērķu sasniegšanai: Krievijai- suverenitāte, Latvijai- neatkarība, tādēļ valdību abpusējās attiecības skatītas Baltijas, kā arī PSRS attiecību kontekstā. Pētījumā attēlots vēsturiski specifisku, labu attiecību fenomens Latvijas un Krievijas starpā, apstākļos, kad izvirzītie mērķi abām valstīm pārklājās. Tāpat sazīmēti potenciālie konflikta momenti, kas pēc neatkarības atgūšanas kļuva par realitāti. Darbs balstīts uz publicētajiem vēsturiskajiem avotiem un zinātnisko literatūru un attiecīgās problēmas analizētas raugoties no reālpolitiskas un institucionālisma skolām.

The subject of the work “The Relations Between Republic of Latvia and Federation of Russia in the Period from 4th of May of 1990 till 21st of August, 1991” are relations between governments of Latvia and Russian Federation in the period of the dual power in the Republic of Latvia during the period from 4th of May, 1990, when the independence of Latvia was declared, to 21st of August, 1991, when the Parliament of Latvia adopted the Constitutional law about the national status, and thus – restored the independence of Latvia entirely. The author of the work deals with the question of the cooperation between the governments of Latvia and Russia regarding the centre of USSR to achieve their goals: for Russia -sovereignity, for Latvia – independence. Therefore the relations between the governments of Latvia and Russia are reviewed in the context with the relations among Baltic states and USSR.The phenomen of historiaclly specific, good relations between Russia and Latvia in the situations of common goals is analysed, as well as potential conflict moments, which became reality after the restoration of the independence of Latvia. The research is based on published historical sources and literature. Problems are analysed from two points - realpolitical and institutional schools.
Relations between the Republic of Latvia and the Russian Federation in the Period from May 4, 1990 - August 21, 1991
Keywords: Vēsture